2014
DOI: 10.1021/mp400681n
|View full text |Cite
|
Sign up to set email alerts
|

Penetratin, a Potentially Powerful Absorption Enhancer for Noninvasive Intraocular Drug Delivery

Abstract: Intraocular drug delivery is extraordinarily hampered by the impermeability of defensive barriers of the eye. In this study, the ocular permeability of fluorophore-labeled cell-penetrating peptides (CPPs), including penetratin, TAT, low molecular weight protamine, and poly(arginine)8, was investigated based on multilevel evaluations. The human conjunctival epithelial cell (NHC) was exposed to various CPPs to determine the cytotoxicity and cellular uptake. Ex vivo studies with rabbit cornea were performed using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
73
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(75 citation statements)
references
References 47 publications
2
73
0
Order By: Relevance
“…In a comparison of the Tat, penetratin, low molecular weight protamine, and poly-arginine CPPs, Liu et al found that all CPPs tested were more permeable across excised corneas than was a control peptide, with penetratin being the most efficient. 27 When applied in vivo in rats, penetratin accumulated strongly in the corneal epithelium and endothelium and was diffusely localized in the stroma. Tat was shown to deliver acidic fibroblast growth factor into the retina and protect from ischemia-reperfusion injury after topical administration in a rat model.…”
Section: Journal Of Ocular Pharmacology and Therapeuticsmentioning
confidence: 99%
“…In a comparison of the Tat, penetratin, low molecular weight protamine, and poly-arginine CPPs, Liu et al found that all CPPs tested were more permeable across excised corneas than was a control peptide, with penetratin being the most efficient. 27 When applied in vivo in rats, penetratin accumulated strongly in the corneal epithelium and endothelium and was diffusely localized in the stroma. Tat was shown to deliver acidic fibroblast growth factor into the retina and protect from ischemia-reperfusion injury after topical administration in a rat model.…”
Section: Journal Of Ocular Pharmacology and Therapeuticsmentioning
confidence: 99%
“…The zeta potentials of Penetratin, Tat, and Arg8 have been reported to be +8, +9, and +9, respectively. 12 From the CPP screening tests, Arg8 revealed higher cellular uptake despite a similar positive charge density compared with Penetratin and Tat. It has been reported that the uptake efficiency is attributed to the guanidinium head group of the Arg side chain rather than the positive charge alone.…”
Section: Discussion Cpp Nanoparticlesmentioning
confidence: 96%
“…Although the possibility of Arg8 as a permeability enhancer was evaluated through the round window membrane, 11 three kinds of CPPs (Penetratin, Tat, and Arg8) were compared as inner ear delivery enhancers. 12,13 Dexamethasone (Dex), a type of steroid, has been reported to have transient dilatory effects on nuclear pores, expanding up to 135 nm in diameter. 14,15 Therefore, the presence of Dex enhances the gene transfection efficiency in cells, where Dex binds to the glucocorticoid receptor in the cytosol, [16][17][18] and confers protective effects on cochlear cells against inflammation in the inner ear, such as sudden sensorineural hearing loss through its antiinflammatory effects.…”
mentioning
confidence: 99%
“…Examination of the literature shows that poly-arginine-based CPPs have been tested extensively against many cell types, with reports conflicting whether CPPs inflict toxic effects on cells. [37][38][39] Here, topical delivery by eye drop delivered 5 mg/mL CPP onto the cornea, with 85 lg/mL calculated to be present in the posterior segment after 30 minutes, based on the detected presence of the anti-VEGF. These values were then used to provide the concentration range to test toxicity on cultured rodent and human ocular cells.…”
Section: Discussionmentioning
confidence: 99%